Innovation's Role In Entrepreneurship: The Power Of Knowledge And Creativity In Shaping Entrepreneurial Aspirations - Ruth Theressa Sitinjak; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to in vestigate the influence of entrepreneurial knowledge and entrepreneurial creativity on entrepreneurial intention. The research employs a quantitative measurement approach to assess the impact of entrepreneurial knowledge and entrepreneurial creativity on entrepreneurial intention. The measurement scale used is the Likert scale. The type and source of data for this research are derived from primary data collection. Primary data is information collected directly from respondents through a structured questionnaire. The questionnaire was distributed during the data collection process of this research. The study was conducted by analyzing data from a number of respondents involved in the entrepreneurial context. A survey method was used to gather data from 99 respondents with diverse backgrounds. The analysis method employed was the quantitative analysis of the Inner Model, with calculations of T statistics, R-Square, f-Square, and VIF using SmartPLS version 4.0.9.3. The Outer Model was assessed for Convergent Reliability, Discriminant Validity, Composite Reliability, and Cronbach's Alpha. The research results indicate that entrepreneurial knowledge has a positive and significant influence on entrepreneurial intention. Additionally, entrepreneurial creativity was also found to have a positive and significant impact on entrepreneurial intention. Enhancing entrepreneurial knowledge and promoting creativity can be effective strategies to stimulate entrepreneurial intention in society.